Low-pass spatial filter based on 3D metamaterial rasorber with wideband absorption at high frequency - X. Q. Jia; Q. Chen; Q. An; Y. J. Zheng; Y. Q. Fu (AIP Advances, 2020)
This paper presents the design and analysis of a low-pass spatial filter which has wideband absorption at high frequency using a 3D metamaterial rasorber (MR). The unit cell of the 3D MR is composed of several stacked layers of square patches with tapered dimensions, which are separated by thin lossy dielectric laminas. Every two adjacent layers’ metallic patches constitute a resonance cavity, and the inside lossy dielectric substrate results in absorption at the resonance frequency. The stacked metal–dielectric laminas construct a frustum pyramid. With the dimensions of the resonance cavities tapering from the bottom layer to the top layer, the pyramid absorbs over their resonance frequencies so that wideband absorption can be achieved. Besides, the incident wave at the frequencies below all these resonance frequencies can transmit through these cavities. Hence, the pyramid also constructs a low-pass spatial filter. The operation mechanism of this 3D MR structure is analyzed from several aspects by numerical simulation, and experimental measurement has also been executed to verify the design. The 3D metamaterial rasorber performs as an absorber in the Ku-band and a low-pass filter below the X-band. The absorption band with absorptivity higher than 80% spans from 12.3 GHz to 18.2 GHz, and the insertion loss at the frequency below 11.1 GHz is less than 0.9 dB.